An Integral, Risk and Energy Approach in Management Systems. Analysis of ISO 50001: 2018 (2019)
Business progress and human development are linked to the effective management and saving of energy resources. The ISO 50000 family of standards provides practices for the utilization, savings, efficiency and continuous improvement in energy performance, while the ISO 50001 establishes the requirements for an energy management system (EnMS). This document presents i) the main topics of the ISO 50001:2018 and other areas not included in its review; ii) the need for organizations to have a comprehensive model with a risk focus for the rational implementation of management systems that fulfil the practices of energy efficiency, in conjunction with quality, safety, health at work and environmental management, among others; iii) the proposed focus for the conceptual model and the implementation route of a comprehensive management system, "QHSE3+" (Q = quality management (ISO 9001: 2015), HS = health and safety at work (ISO 45001: 2018), E = environmental management (ISO 14001: 2015), E2 = energy efficiency (ISO 50001: 2011) and + = other components of risk), which contributes to the sustainable success of organizations by reducing the vulnerabilities and risks associated with the categories in the acronym QHSE3+..